Clinical and immunological markers of dengue progression in a study cohort from a hyperendemic area in Malaysia - Rathakrishnan, A.; Klekamp, B.; Wang, S.M.; Komarasamy, T.V.; Natkunam, S.K.; Sathar, J.; Azizan, A.; Sanchez-Anguiano, A.; Manikam, R.; Sekaran, S.D. (Public Library of Science, 2014)
Background: With its elusive pathogenesis, dengue imposes serious healthcare, economic and social burden on endemic countries. This study describes the clinical and immunological parameters of a dengue cohort in a Malaysian city, the first according to the WHO 2009 dengue classification. Methodology and Findings: This longitudinal descriptive study was conducted in two Malaysian hospitals where patients aged 14 and above with clinical symptoms suggestive of dengue were recruited with informed consent. Among the 504 participants, 9.3 were classified as non-dengue, 12.7 without warning signs, 77.0 with warning signs and 1.0 with severe dengue based on clinical diagnosis. Of these, 37 were misdiagnosed as non-dengue, highlighting the importance of both clinical diagnosis and laboratory findings. Thrombocytopenia, prolonged clotting time, liver enzymes, ALT and AST served as good markers for dengue progression but could not distinguish between patients with and without warning signs. HLA-A*24 and -B*57 were positively associated with Chinese and Indians patients with warning signs, respectively, whereas A*03 may be protective in the Malays. HLA-A*33 was also positively associated in patients with warning signs when compared to those without. Dengue NS1, NS2A, NS4A and NS4B were found to be important T cell epitopes; however with no apparent difference between with and without warning signs patients. Distinction between the 2 groups of patients was also not observed in any of the cytokines analyzed; nevertheless, 12 were significantly differentially expressed at the different phases of illness. Conclusion: The new dengue classification system has allowed more specific detection of dengue patients, however, none of the clinical parameters allowed distinction of patients with and without warning signs. While the HLA-A*33 may be predictive marker for development of warning signs; larger studies will be needed to support this findings.